1984
DOI: 10.2134/agronj1984.00021962007600040041x
|View full text |Cite
|
Sign up to set email alerts
|

Residue Management in Double‐Crop Conservation Tillage Systems1

Abstract: Crop residues have become an increasingly important renewable natural resource. They can serve to maintain optimum crop production on the nation's severely eroding 45.3 million ha of cropland as well as decrease the increasing cost of synthetic N fertilizer. Conservation tillage technologies have been recently identified as a high priority research need for sustaining agronomic productivity in the humid USA. Three double‐crop tillage systems—spring and fall disking, fall disking, and no‐tillage—were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…Similar results were reported by Langdale et al (1984), Sanford et al (1973), Elkins et al (1980), and Lal (1981. In no-till systems chemicals gave significantly better weed control because the pre-plant application of glyphosate killed existing weeds and the postemergence application of atrazine gave effective residual weed control.…”
Section: Weed Control In Sorghum 119supporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were reported by Langdale et al (1984), Sanford et al (1973), Elkins et al (1980), and Lal (1981. In no-till systems chemicals gave significantly better weed control because the pre-plant application of glyphosate killed existing weeds and the postemergence application of atrazine gave effective residual weed control.…”
Section: Weed Control In Sorghum 119supporting
confidence: 89%
“…Langdale et al (1984) studied residue management in double cropping conservation tillage systems and found that conservation tillage significantly increased yield of grain sorghum when compared to conventional tillage systems. They reported that grain sorghum in rotation with soybeans in double cropping systems increased yield of both sorghum and soybeans.…”
Section: Introductionmentioning
confidence: 99%
“…By leaving more than 30% of the soil surface covered with residues, conservation tillage may reduce the severity of drought stress that occurs during the growing season. For many soils, surface residues can enhance crop productivity by increasing rainfall infiltration into the root zone (1,2), reducing water runoff (12,14), de-829 creasing soil losses (14), and improving soil tilth (10,11). Surface residues may also improve soil water contents by decreasing soil temperature, impeding the diffusion of water vapor from the soil surface, acting as an absorbant for water vapor diffusing from the soil, and reducing wind velocity at the soil surface (7,17).…”
mentioning
confidence: 99%
“…Rice et al (1986) suggested that no-tillage systems in Kentucky reached a state of soil nitrogen equilibrium in approximately ten years. However, soil organic matter (SOM) accumulation under reduced tillage varies considerably with life-zone, soil type, length of time under cultivation, and cropping practices (Hargrove et al, 1982;Langdale et al, 1984;Lugo et al, 1986;Gallaher and Ferrer, 1987). Thus, accumulation of soil organic matter and development of nutrient recycling processes (panel B) may require longer periods of transition in some systems than in others.…”
Section: •Pesticide Residue (B)mentioning
confidence: 99%